Perancangan Fasilitas Gudang Dalam Sistem Logistik (Pendekatan Berbasis Laboratorium) - Nanda Ruswandi; Iwan Sukarno Sukarno; Harummi Sekar Amarilies Sekar Amarilies; Rachmad Inca Liperda; M. Welano Kharisma; Mega Rizkah Sudiar; Raina Fridayanti (Jurnal Logistik Indonesia, 2020)
All of automotive companies around the world are aggressively producing large number of motorized vehicles, especially cars. A car is a transportation mode that is widely used by the middle and upper class. The large number of cars uses cannot be separated from the needs for maintenance of the vehicle itself. Lubricant is the core of engine maintenance on vehicles. Therefore, the demand for lubricants continues to increase due to the increasing demand for cars. Bandar Lampung, for the example, is increasing in the term of the city’s population that is affecting its number of people who own cars. This phenomenon caused the demand for lubricants to increase significantly, so that many lubricant distributors were overwhelmed by this demand. Seeing this opportunity, the RWM Logistics, which is a new Third Party Logistics (3PL) company with value added service is lubricant packaging, has a plan to build a lubricant storage facility in Bandar Lampung. In designing the facility, the company has to decide the layout design, area requirements, material handling planning, and the operational costs. The development of this facility is expected to help the company to meet the demand of lubricant products that were not covered by other distributors.